POTENSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DALAM PENGEMBANGAN PRODUK BURGER PREBIOTIK RASA DAGING PANGGANG - Mawaddah, Alfi; Rossi, Evy; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research was to determine the level of consumer preferences of prebiotic burger with white oyster mushroom (Pleurotus ostreatus) and chicken. The research was carried out by experiment with seven treatments, that were the combination of white oyster mushroom (J) and chicken (A) ; JA1 (0:4), JA2 (1:3), JA3 (2:2), JA4 (3:1), JA5 (4:0), the control JA6 (beef 100%), and control JA7 (commercial chicken burger). Sensory analysis of this research used hedonic test and descriptive test. The results of cluster analysis (AHC) from hedonic test and analysis of Principal Component Analysis (PCA) from descriptive test were analyzed used preference mapping. The best treatment in this research was JA2 (oyster mushroom 1:3 chicken) with the level of consumer preference by 57% that have characteristic garlic flavor, garlic taste, barbeque flavor, barbeque taste, and chicken taste. Keywords: Prebiotic burger, oyster mushroom, chicken, consumer preference, preference mapping